High test-retest-reliability of pain-related evoked potentials (PREP) in healthy subjects. (24th April 2017) - Özgül, Özüm Simal; Maier, Christoph; Enax-Krumova, Elena K.; Vollert, Jan; Fischer, Marc; Tegenthoff, Martin; Höffken, Oliver
Highlights: Pain-related evoked potentials (PREP) are an established method to examine A-delta fibre function. We determined test-retest-reliability and side-to-side differences (dorsum of both hands) of PREP in healthy subjects. PREP shows an excellent test-retest-reliability, negligible side differences. Abstract: Pain-related evoked potentials (PREP) is an established electrophysiological method to evaluate the signal transmission of electrically stimulated A-delta fibres. Although prerequisite for its clinical use, test-retest-reliability and side-to-side differences of bilateral stimulation in healthy subjects have not been examined yet. We performed PREP twice within 3–14 days in 33 healthy subjects bilaterally by stimulating the dorsal hand. Detection (DT) and pain thresholds (PT) after electrical stimulation, the corresponding pain ratings, latencies of P0, N1, P1 and N2 components and the corresponding amplitudes were assessed. Impact of electrically induced pain intensity, age, sex, and arm length on PREP was analysed. MANOVA, t -Test, interclass correlation coefficient (ICC), standard error of measurement (SEM), smallest real difference (SRD), Bland-Altmann-Analysis as well as ANCOVA were used for statistical analysis. Measurement from both sides on both days resulted in mean N1-latencies from 142.39 ± 18.12 ms to 144.03 ± 16.62 ms and in mean N1P1-amplitudes from 39.04 ± 12.26 μV to 40.53 ± 12.9 μV. Analysis of a side-to-side effect showed for the N1-latency a F-value of 0.038 and for the N1P1-amplitude of 0.004 (p > 0.8). We found intraclass correlation coefficients (ICC) from 0.88 to 0.93 and a standard error of measurement (SEM) < 10% of mean values for all measurements concerning the N1-Latency and N1P1-amplitude. Intraclass correlation coefficients, standard error of measurement and Bland-Altman-Analyses revealed excellent test-retest-reliability for N1-latency and N1P1-amplitude without systematic error and there was no side-to-side effect on PREP. N1-latency (r = 0.35, p < 0.05) and N1P1-amplitude (r = −0.45, p < 0.05) correlated with age and additionally N1-latency correlated with arm length (r = 0.45, p < 0.001). In contrast, pain intensity during the stimulation had no effect on both N1-latency and N1P1-amplitude. In summary, PREP showed high test-retest-reliability and negligible side-to-side differences concerning the commonly used parameters N1-latency and N1P1-amplitude.